PENGARUH TEORI PERUNDANG-UNDANGAN TERHADAP DINAMIKA NORMA HUKUM DALAM SISTEM HUKUM INDONESIA - Utami, Tanti Kirana; Lananda, Ardelia; Simbolon, Cindy Claudia; Rahmah, Mila Arastasya; Baidhowi, Nayla Ratu; Januwati, Pusfa (LPPM Universitas Doktor Husni Ingratubun Papua, 2024)
The theory of legislation in the formation and change of law in Indonesia has a very important position. This is because the theory of legislation can provide structure and direction for the development of effective law and in accordance with the needs of society. In Indonesia, the theory of legislation aims to create a legal system that is in accordance with the principles of the rule of law and Pancasila. The purpose of this study is to analyze in more depth the Influence of the Theory of Legislation on the Dynamics of Legal Norms in the Indonesian Legal System. The approach method in this study is to use a normative juridical approach, namely a legal research method that examines library materials or secondary data. The identification of problems in this study is the Influence of the Theory of Legislation on the Quality of Implementation of Legal Norms in Indonesia, Factors that Influence the Application of the Theory of Legislation in the Practice of Legal Formation in Indonesia, and the Impact of the Application of the Theory of Legislation on the Stability of Legal Norms in the Legal System in Indonesia. The application of the theory of legislation in Indonesia aims to create systematic, fair, and effective regulations by involving community participation. Therefore, comprehensive reform of the legal system and transparent and professional law enforcement are essential to improve the quality of legal norms and strengthen public trust in the justice system.